WAYANG KULIT WONG KOMUNITAS LIMA GUNUNG: KAJIAN TEKS DRAMA DALAM SEMIOTIKA TEATER - Prasena Arisyanto (Universitas PGRI Semarang, 2017)
AbstractThis research aim to analyze wayang kulit wong performance from dramatic text or manuscript. The manuscript that analyze taken from story of Menjunjung Langit Mencium Bumi. As analyzing concept it used theatre of semiotic from Tadeus Kowzan that focussed in dramatic text analyzing. Research method is qualitative method with theatre semiotic approach. Data collection techniques use observation, interview, and document study. Research result shows that wayang kulit wong performance not need a manuscript because the player only following instruction from the director so that the performance can go on. So, researchers make a performance transcript as manuscript subtituter. Based on manuscript, there is a meaning in wayang kulit wong performance with story of Menjunjung Langit Mencium Bumi. The meaning related to Sumpah Pemuda commemoration as frame of program. Manuscript of Menjunjung Langit Mencium Bumi story also has an uniqueness of plot, figure character, and dialogue.